Cognitive disorders in patients with atrial fibrillation: A review - Vladimir A. Parfenov (ZAO "Consilium Medicum", 2023)
Cognitive disorders (CD) represent one of the leading causes of disability among the elderly. Atrial fibrillation (AF) is an independent and corrected risk factor for CD and dementia. The development of CD with AF is associated with the occurrence of cerebral infarcts, silent infarcts, cerebral micro and macro hemorrhages, a cerebral small vessels disease, cerebral hypoperfusion, and comorbid neurodegenerative disease. The prevention of the first and recurrent ischemic stroke (IS) is the leading importance in preventing the development and progression of the CD in AF, which include the use of the vitamin K antagonists (VKA) and new oral anticoagulants (the NOACs apixaban, dabigatran, rivaroxaban, edoxaban), control of arterial pressure and other methods of prevention. The use of the NOACs is more effective than using VKA, reduces the risk of CD and dementia. The use of individual NOACs, various methods for the prevention of CD and Alzheimer's disease in patients with AF are discussed.